PERENCANAAN SISTEM PLTS SEBAGAI SOLUSI UNTUK MEMENUHI KEBUTUHAN ENERGI LISTRIK PADA PERAHU NELAYAN DI PANTAI KELAN KUTA - Namira Purnama Noor Firdaus; Agus Putu Abiyasa (Jurnal Pendidikan Teknik Elektro Undiksha, 2026)
Fishing boats still rely on generators to meet their electricity needs, resulting in dependence on fossil fuels and greenhouse gas emissions. This study aims to design an off-grid solar power system for fishing boats at Kelan Beach, Kuta. The design is based on a load consisting of three 200 W LED lights operating for 10 hours, requiring 6 kWh/day. The system uses six SP400M-54 monocrystalline solar modules, rated at 400 Wp, with a capacity of 2.4 kWp, a 48 V 200 Ah battery system comprising two Pylontech US5000 100 Ah units, a Victron SmartSolar MPPT 150/60, and a Victron Phoenix 48/1600 inverter. Manual calculations estimate annual energy production at 3,499 kWh, while PVsyst simulation produces 3,693 kWh/year, differing by 194 kWh/year or 5.54%. The simulation indicates a Performance Ratio of 44.2% and Solar Fraction of 99.7%, while reducing gasoline consumption by 1,320 liters/year and emissions by 3.16 metric tons CO₂/year.